Analysis of customer satisfaction using Total Quality Management (TQM) junior high school - Hasanah, Eka Huswatun; Kholid, Idham; Yetri, Yetri (Journal of Advanced Islamic Educational Management, 2021)
To develop the potential of students must be supported by quality education. Total Quality Management becomes a management approach centered on quality for long-term success through customer satisfaction. The purpose of this study is to find out how customer satisfaction is assessed from aspects of tangibles (direct evidence), reliability, responsiveness, assurance, and empathy. This research uses mixed methods with the Embedded Concurrent model (unbalanced mixture), applied to students with a sample of 90 students as respondents chosen randomly with 25 items of questions, observations, interviews, documentation. The findings of these study address customers getting satisfaction with the services provided by schools. With responsiveness aspects that are more prominent than other elements.